Reconstructing the professional domain: Boundary work of professionals and volunteers in the context of social service reform. (May 2018) - van Bochove, Marianne; Tonkens, Evelien; Verplanke, Loes; Roggeveen, Suzanne
Shifts from professionals to volunteers are observed across national contexts and in various types of public services, particularly in long-term care and social work. This article examines how professionals and volunteers in the Netherlands perform boundary work to construct, maintain and dissolve boundaries between them in the context of social service reform. Two types of boundary work were found: demarcation work and welcoming work. Demarcation work relates to a situation where differences in knowledge, authority and reliability between professionals and volunteers are emphasised. Welcoming work involves the efforts of professionals to welcome specific volunteers to their professional domain. This study examines the implications of the second type of boundary work for structural characteristics of the social service sector. It concludes that although welcoming work can lead to deprofessionalisation, it can also promote the professionalisation of nurses and social workers.